Discovery of gastric inhibitory polypeptide and its subsequent fate: Personal reflections - Pederson, Raymond A (J Diabetes Investig, 2016)
The present review focuses initially on experimental studies that were designed to identify acid inhibitory factors, referred to as ‘enterogastrones,’ that ultimately led to the isolation of gastric inhibitory polypeptide (GIP), a 42‐amino acid polypeptide. GIP was shown to inhibit acid secretion in animal models, as well as stimulating gastric somatostatin secretion. However, its role in human gastric physiology is unclear. Further studies showed that GIP strongly stimulated the secretion of insulin, in the presence of elevated glucose, and this ‘incretin’ action is now considered to be its most important; an alternative for the GIP acronym, glucose‐dependent insulinotropic polypeptide, was therefore introduced. In the 1970s, GIP purified by conventional chromatography was shown by high‐performance liquid chromatography to consist largely of GIP (1‐42) and GIP (3‐42). It was later shown that dipeptidyl peptidase 4 was a physiologically relevant enzyme responsible for this conversion, as well as the similar metabolism of the second incretin, glucagon‐like peptide‐1. Dipeptidyl peptidase‐4 inhibitors are currently in use as type 2 diabetes therapeutics, and studies on islet transplantation in rodent models of type 1 diabetes have shown that dipeptidyl peptidase‐4 inhibitor treatment reduces graft rejection. Additional studies on C‐terminally shortened forms of GIP have shown that GIP (1‐30) and a dipeptidyl peptidase‐4‐resistant form (D‐Ala(2) GIP (1‐30)) are equipotent to the intact polypeptide in vitro, and administration of D‐Ala(2) GIP (1‐30) to diabetic rodents greatly improved glucose tolerance and reduced apoptotic cell death in islet β‐cells. There are probably therefore further clinically useful effects of GIP that require investigation.